Duvidoso, ainda que entendido: Perspectivas pornô eróticas sobre a fotoperformance, a escrita criativa e a cena teatral - Alves, Leandro Sousa (2023)
This research examines the intersection between erotic pornography, LGBTQIAPN+ political agendas, performativity, and the acting in contemporary artistic practice. The investigation adopts the emerging paradigm of performative research (HASEMAN, 2006), employing a methodological approach based on bricolage, which incorporates bibliographic and artistic references, as well as creative practice, to explore the specificities of this field of study. The work includes four artistic processes developed during the current period of the program: the series of photoperformances Invertido and Sonho de Valsa, the text Diário de uma bixa, and the play Kamal. Through these processes, I seek to reflect on nudity, eroticism, and transgression in creative experimentations. Thus, this research aims to investigate the relationship between male homoeroticism and the creative act, identify transgressive elements in the inclusion of LGBTQIAPN+ bodies and themes in the contemporary scene, relate eroticism to the development of creative processes, and contribute to the study of practice as research in the Arts. Additionally, the research also reflects on the relationship between systemic violence against the LGBTQIAPN+ population and the erotic field, seeking to understand how these two aspects intertwine. Through this investigation, I examine the complex dynamics between sexuality, politics, and art, finding equivalences between elements of practice and eroticism. I also problematize the distinction between the erotic and the pornographic, challenging the binaries of Art and Life, and reality and fiction in artistic processes. I further present three artistic perspectives in different languages concerning nonnormative sexualities as a political action of a counter-hegemonic social project.